Positive Role of Chinese Herbal Medicine in Cancer Immune Regulation - Wang, Sumei; Long, Shunqin; Deng, Zhiyin; Wu, Wanyin (The American journal of Chinese medicine (1979), 2020)
Complementary and alternative medicine (CAM) plays a critical role in treating cancer patients. Traditional Chinese Medicine (TCM) is the main component of CAM. TCM, especially Chinese Herbal Medicine (CHM), has been increasingly used in China, some other Asian countries and European countries. It has been proven to enhance the efficacy of chemotherapy, radiotherapy, targeted-therapy, and immunotherapy. It lessens the damage caused by these therapies. CHM functions on cancer by inhibiting tumor progression and improving an organism's immune system. Increasing evidence has shown that many CHM exert favorable effects on the immune regulation. We will summarize the role of CHM on patient's immune system when treating cancer patients. Our evidence reveals that single herbs, including their extracts, compound formulations, and preparations, will provide current advances on CHM study, especially from the perspective of immune regulation and novel insights for CHM application in clinic. The main herbs used to treat cancer patients are health-strengthening ( ) herbs and pathogen eliminating ( ) herbs. The key mechanism is regulating the immune system of cancer patients. Firstly, health-strengthening herbs are mainly functioned as immune regulatory effectors on cancer. Secondly, some of the compound formulations mainly strengthen the health of patients by regulating the immune system of cancer patients. Lastly, some Chinese medicine preparations are widely used to treat cancer for their properties of spiriting vital energy and anti-cancer effects, mainly by improving immunity. CHM plays a positive role in regulating patients' immune system, which helps cancer patients to fight against cancer itself and finally improves patients' life quality.